2018
DOI: 10.4081/hpr.2018.7444
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of disordered eating attitudes among adolescent girls in Arar City, Kingdom of Saudi Arabia

Abstract: Eating disorders (ED) are one of the most common psychiatric problems faced by todays adolescent girls where the attitude towards weight and shape as well as their perception of body shape are disturbed. The aim of the paper is to assess the prevalence and associated factors of disordered eating attitudes among adolescent girls of Arar city, Kingdom of Saudi Arabia. This is a cross-sectional survey design in which 314 adolescents females (age: 15-19 years) were selected from four schools of Arar city, KSA. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 21 publications
2
39
2
1
Order By: Relevance
“…Table 2 shows the total score and the scores of each subscale of EAT-26 for all students and for the two groups. The median (IQR) score for all students was 7 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and the median (IQR) scores for dieting, bulimia, and oral control were 5 (2-8), 0 (0-2), and 1 (0-3), respectively. The results of the study showed that 5.4% (26╱483; 95% CI 3.6%, 7.8) of the participants had DEAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows the total score and the scores of each subscale of EAT-26 for all students and for the two groups. The median (IQR) score for all students was 7 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and the median (IQR) scores for dieting, bulimia, and oral control were 5 (2-8), 0 (0-2), and 1 (0-3), respectively. The results of the study showed that 5.4% (26╱483; 95% CI 3.6%, 7.8) of the participants had DEAs.…”
Section: Resultsmentioning
confidence: 99%
“…It is crucial to improve our understanding of the diversity and distinctiveness of EDs in individual countries and how these are related to industrialization and urbanization. 12 According to Japanese national surveys, 13 EDs have increased rapidly from a prevalence rate of 1.18% to 12.74% over the 20-year period from 1982 to 2002 among female university students, as well as the general population. This prevalence rate is getting closer to those of Western countries due to Western cultural influences on Japanese society that emphasize dieting to achieve a thin body.…”
Section: Introductionmentioning
confidence: 99%
“…As Saudi Arabia and other countries in the Middle East undergo epidemiologic transition and cultural change, the burden of EE is rising [ 25 ]. While anxiety, stress, and depression are central instigators of EE, few studies have been conducted to assess anxiety [ 26 ] and depression [ 27 ] in the general Middle Eastern population, and this type of mental health research is still lacking in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…In a representative community survey, Michalak et al confirmed the association between vegetarianism and eating disorders [ 17 ]. Accordingly, a positive association between being a vegetarian and diagnosis [ 13 ] or indication (according to EAT-26 [ 12 , 15 , 20 , 21 ] and EAT-40 scores) [ 14 ] of an eating disorder has been reported by other researchers.…”
Section: Resultsmentioning
confidence: 89%
“…The literature search produced a total of 1271 results, after removal of duplicates; of them 1235 were deemed irrelevant from title and abstract, whereas 36 were evaluated in full-text. Among the latter, 16 were excluded due to various reasons and ultimately, a total of 20 studies (14.391 subjects) published between 1986 and 2019 were included in the present systematic review [ 7 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The PRISMA flowchart describing the successive steps in the selection of studies is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%